Reconstruction of Senior High School Laboratory Activity Design on Motion System Materials - Jacinda, Alma Aliya; Supriatno, Bambang (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to provide an overview of the motion system practicum design used in SMA and the subject of this research is the laboratory activity design of the motion systems laboratory activity design used in schools. This research is a qualitative descriptive study. The samples in this study were 3 samples of motion system in hard bone structure sub-material laboratory activity design, which were taken using a purposive sampling technique. This study uses an instrument developed based on the Vee Diagram component scoring table adapted from Novak and Gowin's book. Based on the instruments developed, the results of the analysis of this practicum student worksheet have several problems in terms of 1) the suitability of the student worksheet components, not yet following the demands of the 2013 Basic Curriculum Competency, and the title and objectives are not following the work steps and are not relevant to the object/phenomenon that appears so that causing this practicum to be difficult to execute, 3) construction of knowledge, questions have not led to phenomena that arise, are not connected with data interpretation and the conclusions that are built do not yet describe the title and objectives of the practicum. Meanwhile, based on the results of the analysis of the Vee Diagram scoring instrument, shows that the components of focus questions, objects/ events, concepts/ theories/ principles, transformation notes, and knowledge claims have not yet reached the maximum score so the circulating practicum worksheets do not support the Vee Diagram by Novak & Gowin components optimally so it needs to be reconstructed.